2014
DOI: 10.1155/2014/747014
|View full text |Cite
|
Sign up to set email alerts
|

PPARα: A Master Regulator of Bilirubin Homeostasis

Abstract: Hypolipidemic fibrates activate the peroxisome proliferator-activated receptor (PPAR) α to modulate lipid oxidation and metabolism. The present study aimed at evaluating how 3 PPARα agonists, namely, fenofibrate, gemfibrozil, and Wy14,643, affect bilirubin synthesis and metabolism. Human umbilical vein epithelial cells (HUVEC) and coronary artery smooth muscle cells (CASMC) were cultured in the absence or presence of the 3 activators, and mRNA, protein, and/or activity levels of the bilirubin synthesizing heme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Others have proposed that PPARα may regulate bilirubin homeostasis [67]. These observations suggest a possible feedback loop for bilirubin-PPARα, which might be a fundamental circuit for exercise.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Others have proposed that PPARα may regulate bilirubin homeostasis [67]. These observations suggest a possible feedback loop for bilirubin-PPARα, which might be a fundamental circuit for exercise.…”
Section: Discussionmentioning
confidence: 95%
“…There has been a correlation for palmitoylethanolamide (PEA) and oleoylethanolamine (OEA), which are natural PPARα ligands derived from fatty acids, and their activation of PPARα may regulate bilirubin levels [ 66 ]. Others have proposed that PPARα may regulate bilirubin homeostasis [ 67 ]. These observations suggest a possible feedback loop for bilirubin-PPARα, which might be a fundamental circuit for exercise.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there is no literature available on a possible role for the UGT1A1 * 28 polymorphism and/or elevated levels of UCB in these complex regulations. As yet, only one recent study 31 points out a connection between circulating bilirubin (BR) and Ppar α, using an in vitro approach. This very report expands the field of known physiological bilirubin functions and activities, including antioxidant 32 , immune-modulating 33 and signalling effects, the latter of which have been investigated in terms of Ppar activities in BR-treated mice.…”
mentioning
confidence: 99%
“…Investigations based on cell cultures indicate that PPARα activators, such as fenofibrate and gemfibrozil, regulate genes controlling bilirubin synthesis in vascular cells and its metabolism in hepatic cells [ 32 ], providing beneficial antiatherosclerotic effects, essentially by the upregulation of HMOX1. Furthermore, it has been demonstrated that patients with Gilbert’s polymorphism and higher bilirubin levels are less affected by metabolic disorders, such as obesity and type 2 diabetes mellitus [ 2 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%